4X+3-5+2X=20-3X+12

Simple and best practice solution for 4X+3-5+2X=20-3X+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4X+3-5+2X=20-3X+12 equation:


Simplifying
4X + 3 + -5 + 2X = 20 + -3X + 12

Reorder the terms:
3 + -5 + 4X + 2X = 20 + -3X + 12

Combine like terms: 3 + -5 = -2
-2 + 4X + 2X = 20 + -3X + 12

Combine like terms: 4X + 2X = 6X
-2 + 6X = 20 + -3X + 12

Reorder the terms:
-2 + 6X = 20 + 12 + -3X

Combine like terms: 20 + 12 = 32
-2 + 6X = 32 + -3X

Solving
-2 + 6X = 32 + -3X

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '3X' to each side of the equation.
-2 + 6X + 3X = 32 + -3X + 3X

Combine like terms: 6X + 3X = 9X
-2 + 9X = 32 + -3X + 3X

Combine like terms: -3X + 3X = 0
-2 + 9X = 32 + 0
-2 + 9X = 32

Add '2' to each side of the equation.
-2 + 2 + 9X = 32 + 2

Combine like terms: -2 + 2 = 0
0 + 9X = 32 + 2
9X = 32 + 2

Combine like terms: 32 + 2 = 34
9X = 34

Divide each side by '9'.
X = 3.777777778

Simplifying
X = 3.777777778

See similar equations:

| x(3x-2)=12x^2-2x-1 | | 9x-16=-205 | | -12x^7-4x^6= | | 7m^2+63m=0 | | -0.16-5=.66x | | -3x+8x-9=5(x-6)-3 | | -.16-5=.6x | | 3(2x-5)=7x | | f(9)=9x-4 | | 2x+17=6x+5 | | .75x-1=.5x+7 | | 8x-21=7x+14 | | 10+9b=1 | | 5x^2-33x-10=0 | | 5.6-x=3.7 | | y=4x+100 | | -52x-12=6x+2x+4 | | y=2x+200 | | px+q=rx+5 | | 2*x^2+18*x-4=0 | | 60+(x-10)=180 | | 7x-34=2x+97 | | 24x^2=6x+9 | | 7x-18=8x-11 | | P^3-2p^2-8p=0 | | X^7+128=0 | | 2sinx+3=2.5 | | 8x-15=3x+9 | | 4x+23=80 | | log(x^3)-2*log(x)=2 | | X*-6x=0 | | lg(x^3)-2lg(x)=2 |

Equations solver categories